BALINESE SCRIPT KEYBOARD FOR MOBILE DEVICES: ENHANCING DIGITAL ACCESSIBILITY AND CULTURAL PRESERVATION - Pramartha, Cokorda Rai Adi; Arka, I Wayan; Iswara, Ida Bagus Ary Indra; Supriana, I Wayan; Giri, Gst. Ayu Vida Mastrika; Suhartana, I Ketut Gede (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
The Balinese script, integral to Bali's cultural heritage, faces challenges in digital representation. This study introduces a mobile keyboard prototype specifically designed for the Balinese script, featuring a non-QWERTY, multi-layered layout and long-press functionality to accommodate its complex characters. Using the Design Science Research Methodology (DSRM), the research involved problem identification, prototype development, and usability evaluation. Internal testing with selected users revealed an average ease-of-use score of 4.8 and a usefulness score of 4.4 on a 7-point Likert scale, demonstrating the keyboard’s practicality for communication and educational use. Key features, including logical character organization and efficient input for diacritics, were positively received, though further refinements such as optimizing layout and adding predictive text are needed. This prototype highlights the potential of digital tools to preserve endangered scripts by integrating them into modern technology. Future work will focus on expanding features, supporting dialect variations, and extending the model to other indigenous scripts. This research contributes to digital heritage preservation, offering a framework for revitalizing traditional scripts through user-centered design and technology integration.